Sustainability of physical exam skills in a resident-led curriculum in a large internal medicine program with competency based medical education - Thiwanka Wijeratne, Don; Srivastava, Siddhartha; Chan, Barry; Hopman, Wilma; Thomson, Benjamin (Revue canadienne de l'éducation médicale, 2018)
Background: Competency Based Medical Education (CBME) designates physical examination competency as an Entrustable Professional Activity (EPA). Considerable concern persists regarding the increased time burden CBME may place on educators. We developed a novel physical examination curriculum that shifted the burden of physical examination case preparation and performance assessment from faculty to residents. Our first objective was to determine if participation led to sustainable improvements in physical examination skills. The second objective was to determine if resident peer assessment was comparable to faculty assessment. Methods: We selected physical exam case topics based on the Objectives of Training in the Specialty of Internal Medicine as prescribed by the Royal College of Physicians and Surgeons of Canada. Internal Medicine residents compiled evidence-based physical exam checklists that faculty reviewed before distribution to all learners. Physical exam practice sessions with whole-group demonstration followed by small-group practice sessions were performed weekly. We evaluated this pilot curriculum with a formative OSCE, during which a resident peer and a faculty member simultaneously observed and assessed examinee performance by . Results: Participation in the novel curriculum practice sessions improved OSCE performance (faculty score mean 78.96 vs. 62.50, p<0.05). Peer assessment overestimated faculty scores (76.2 vs. 65.7, p<0.001), but peer and faculty assessments were highly correlated (R2 = 0.73 (95% CI 0.50-0.87). Conclusion: This novel physical examination curriculum leads to sustainable improvement of physical examination skills. Peer assessment correlated well with the gold standard faculty assessment. This resident-led physical examination curriculum enhanced physical examination skills in a CBME environment, with minimal time commitment from faculty members.